PENGARUH KEBIJAKAN DIVIDEN DALAM MEMEDIASI RETURN ON ASSET DAN FIRM SIZE TERHADAP RETURN SAHAM (Studi Pada Perusahaan Yang Tergabung Dalam LQ45 di Bursa Efek Indonesia (BEI) Tahun 2011 – 2014) - Riawan Riawan (ITB AAS INDONESIA, 2017)
This study was conducted to examine the influence of fundamental factors of ROA and firm size on dividend policy. And furthermore the influence of profitability, liquidity and dividend policy to return stock in companies incorporated in the LQ45 listed on the Indonesia Stock Exchange for the period 2011-2014. The sampling technique used in this research is purposive sampling with criteria : (1) It is listed in Indonesia Stock Exchange 2011-2014. (2) It is always seem annual financial statements for the period 2011-2014. (3) It is always pay dividends. The data required in this study were drawn from the Indonesian Capital Market Directory (ICMD) from 2011 to 2014 consisting of 16 companies. Multiple regression analysis of the data. Hypothesis test used the t-statistic at the 5% significance level. The results showed ROA, firm size and dividend policy have a significant effect on stock returns. These results indicate that the performance of the fundamental factors of profitability, firm size and dividend policy on stock returns are used by investors to predict stock returns companies incorporated in the LQ45 listed in Indonesia Stock Exchange in 2011-2014. Key Words: Stock Return, dividend policy, ROA, firm size